Caregiver feeding practices for infants and toddlers and their eating behaviors in Singapore - Quah, Phaik Ling; Chan, Daniel Wei Keong; Loy, See Ling; Ong, Chengsi; Tan, Chai-Hoon Nowel; Chia, Michael Yong Hwa; Chua, Terence Buan Kiong; Yap, Fabian; Chua, Mei Chien; Tan, Kok Hian (Frontiers in Nutrition, 2025)
IntroductionResearch on early childhood caregiver feeding practices and eating behaviors is limited, especially within Asian populations. This study examined these practices across key feeding domains of variety, autonomy, and mealtime setting and timing, stratified by three age groups: 0 to <7 months, 7 to <13 months, and 13 to <36 months.MethodsA cross-sectional survey of 1,307 caregivers from a multi-ethnic population in Singapore captured demographic data, feeding practices, child eating behaviors, and caregivers’ knowledge, attitudes, and practices. One-way analysis of variance (ANOVA), independent T-tests and the chi-square test were used to assess feeding practices and eating behaviors across age groups.ResultsRegarding dietary variety, 14.8 and 6.1% of infants aged 7 to <13 months were offered three or fewer food groups frequently and daily, respectively. Additionally, 11.9% of infants were receiving processed foods often. At this age, only 1.0% of infants were consuming sugar-sweetened beverages (SSBs) often, while 2.0% consumed them daily. Among older children (aged 13 to <36 months), 8.1% were offered a limited variety of three food groups, while 4.5% were offered fewer than three. In contrast, a significantly higher proportion frequently consumed processed foods (24.0%) and sugar-sweetened beverages (25.2%; p < 0.05). In terms of autonomy, only 75.4% of infants (7– < 13 months) and 89.5% of older children (13– < 36 months) were able to self-feed. Caregivers of older children (13– < 36 months) were less likely to recognize hunger and satiety cues compared to those of infants (0–< 13 months; p < 0.05). Older children (13– < 36 months) also more frequently required special mealtime settings (36.6%), viewed screens during meals (29.9%), and were less likely to be offered post-midnight meals nightly (22.6% compared to infants; 70.3%; 0–< 13 months; p < 0.05).ConclusionThese findings underscore the need for culturally tailored educational interventions to improve suboptimal feeding practices in children under three in Singapore’s multiethnic population.